PENINGKATAN AKTIVITAS ANTIJAMUR CANDIDA ALBICANS SALEP MINYAK ATSIRI DAUN SIRIH (Piper bettle LINN.) MELALUI PEMBENTUKAN KOMPLEKS INKLUSI DENGAN B-SIKLODEKSTRIN - Ika Yuni Astuti; Dwi Hartanti; Ani Aminiati (Majalah Obat Tradisional, 2010)
The Piper betle leaf essential oil have antimicrobial activity to Candida albicans (Wirna, 2006). However, the essential oil is unstable to high temperature, light, and oxygen. One approach to improve the stability and facilitate in developing  various dosage forms is by preparing the essential oil in complex inclusion using β-cyclodextrin (Szejtli, 1989). The aim of the present study  was to investigate the effect of inclusion complex formation of the Piper betle leaf essential oil in b-cyclodextrin formulated to polyethylene glicol ointment to antifungal candida albicans activity.  The essential oil of Piper betle leaf was isolated by destillation. The inclusion complex of the essential oil - β-cyclodextrin was prepared by coprecipitation of the essential oil : β- cyclodextrin 1:1 (w/w). The inclusion complex formation was studied with thin layer chromatography (TLC) and powder X-ray diffraction (XRD). In the TLC, sillica gel was used as solid phase, whereas toluen-ethyl acetate (7:3) and methanol-water (7:3) was used as mobile phase, then the Rf value of the essential oil and inclusion complex was compared. The XRD pattern of β-cyclodextrin, physical mixtures and inclusion complex was compared, too. Then, the  polyethylene glicol ointment of the essential oil and inclusion complex was prepared. The physical properties and antifungal activity was compared. The TLC result showed that the essential oil of Piper betle leaf with methanol-water (7:3) as mobile phase had Rf 0,69 and the inclusion complex had Rf 0,81. With toluen-ethyl acetate (7:3), Rf of the essential oil were 0,63; 0,73; 0,85, whereas the inclusion complex were 0,66; 0,80, and 0,91. The powder XRD analysis showed that the pattern of β-cyclodextrin, physical mixture and inclusion complex were different. The differences of Rf from TLC and XRD patterns were showed that  the Piper betle leaf essential oil was complexed with β cyclodextrin. The physical properties studies showed that the homogenity of both formulation was good.  The inclusion complex ointment had spreading property, adhering property and antifungal activity which better than the essential oil ointment. The potency of antifungal activity of the inclusion complex of the essential oil - β-cyclodextrin was not significant different than miconazol ointment.